Rectal Perforation following High-Pressure Distal Colostogram - Giulia Brisighelli; Liam Lorentz; Tanyia Pillay; Christopher J. Westgarth-Taylor (Georg Thieme Verlag KG, 2020)
In patients with anorectal malformations and a colostomy, the high-pressure distal colostogram is the technique of choice to determine the type of malformation and thus to plan the surgical repair. Perforations associated with high-pressure distal colostograms are very rare. The aim of our study was to identify pitfalls to prevent perforation secondary to high-pressure distal colostogram. The study included two male patients and was complicated with rectal perforations secondary to high-pressure distal colostogram. Both patients had an imperforate anus without a fistula. One patient had extraperitoneal rectal perforation with progressive contrast spillage into the peritoneum and demised. The other patient developed an extraperitoneal perforation and an associated necrotizing fasciitis of his perineum and scrotum, but he recovered well after debridement. Two further cases of rectal perforation have been described in the literature. Rectal perforation, although rare, is a described life-threatening complication secondary to high-pressure distal colostogram. The cause is excessive contrast pressure. Injection of contrast should be stopped once the distal end of the colon has a convex shape. Intraperitoneal perforation may cause hypovolemic/septic shock, and patients need to be appropriately resuscitated and should undergo laparotomy. Extraperitoneal perforation requires close monitoring for possible local complications, which may necessitate early debridement.